Recognizing events 4.0: the digital maturity of events. Issue 1 (21st February 2020) - Ryan, William Gerard; Fenton, Alex; Ahmed, Wasim; Scarf, Phillip
Abstract : Purpose: The purpose of this research is to explore and define the digital maturity of events using the Industry 4.0 model (I4.0) to create a definition for Events 4.0 (E4.0) and to place various relevant technologies on a scale of digital maturity. Design/methodology/approach: In a mixed methods approach, we carried out a qualitative social media analysis and a quantitative survey of tourism and events academics. These surveys and the thorough literature review that preceded them allowed us to map the digital technologies used in events to levels of a digital maturity model. Findings: We found that engagement with technology at events and delegate knowledge satisfactorily coexists for and across a number of different experiential levels. However, relative to I4.0, event research and the events industry appear to be digitally immature. At the top of the digital maturity scale, E4.0 might be defined as an event that is digitally managed; frequently upgrades its digital technology; fully integrates its communication systems; and optimizes digital operations and communication for event delivery, marketing, and customer experience. We expect E4.0 to drive further engagement with digital technologies and develop further research. Originality/value: This study has responded to calls from the academic literature to provide a greater understanding of the digital maturity of events and how events engage with digital technology. Furthermore, the research is the first to introduce the concept of E4.0 into the academic literature. This work also provides insights for events practitioners which include the better understanding of the digital maturity of events and the widespread use of digital technology in event delivery.